The Impact of COVID-19 on Healthcare Services in Bangladesh: A Qualitative Study on Healthcare Providers’ Perspectives - Sharmin Parveen; Md. Shahriar Mahbub; Nasreen Nahar; K. A. M. Morshed; Nourin Rahman; Ezzat Tanzila Evana; Nazia Islam; Abu Said Md. Juel Miah (Journal of Preventive Medicine and Public Health, 2024)
Objectives: The objective of this study was to explore healthcare providers’ experiences in managing the coronavirus disease 2019 (COVID-19) pandemic and its impact on healthcare services. Methods: A qualitative study was conducted with 34 healthcare professionals across 15 districts in Bangladesh. Among the participants, 24 were health managers or administrators stationed at the district or upazila (sub-district) level, and 10 were clinicians providing care to patients with COVID-19. The telephone interviews were conducted in Bangla, audio-recorded, transcribed, and then translated into English. Data were analyzed thematically. Results: Most interviewees identified a range of issues within the health system. These included unpreparedness, challenges in segregating COVID-19 patients, maintaining isolation and home quarantine, a scarcity of intensive care unit beds, and ensuring continuity of service for non-COVID-19 patients. The limited availability of personal protective equipment, a shortage of human resources, and logistical challenges, such as obtaining COVID-19 tests, were frequently cited as barriers to managing the pandemic. Additionally, changes in the behavior of health service seekers, particularly increased aggression, were reported. The primary motivating factor for healthcare providers was the willingness to continue providing health services, rather than financial incentives. Conclusions: The COVID-19 pandemic presented a unique set of challenges for health systems, while also providing valuable lessons in managing a public health crisis. To effectively address future health crises, it is crucial to resolve a myriad of issues within the health system, including the inequitable distribution of human resources and logistical challenges.